The Effectiveness of Stunting Prevention Promotion to Improve Mothers’ Knowledge - Mustikawati, Intan Silviana; Putri, Suci Sri Endah Lestari Mulyanto; Mahadewi, Erlina Puspitaloka; Muniroh, Muniroh; Nurmalasari, Mieke; Sangadji, Namira Wadjir (LPPM Institut Pendidikan Nusantara Global, 2024)
Childhood undernutrition include stunting remains a global public health problem that affects many middle-income countries. Nutrition education generally seeks to increase nutritional knowledge, thereby influencing attitude and practices towards good nutrition. This study aimed to analyze knowledge of stunting prevention before and after stunting prevention promotion in Purwakarta Village, Banten Indonesia. This study was quasi-experimental design with one group pre-posttest in 2023. The population in this study were mothers who had children under five years old in Purwakarta Village, Banten Indonesia. A total of 78 mothers who participated in stunting prevention promotion were selected as a respondent. Data was collected by questionnaire and analyzed using paired-t test. The mean score of stunting prevention knowledge was higher after intervention (Mean= 10,45; SD=0,83) than before intervention (Mean= 6,12; SD= 1,84) and it was statistically significant (p < 0,05). Appropriate nutrition promotion plays a role to inform and remind of stunting prevention behavior.